1996
DOI: 10.1111/j.1365-294x.1996.tb00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of continental and island populations of Bombus terrestris (Hymenoptera: Apidae) in Europe

Abstract: Ten microsatellite loci and a partial sequence of the COII mitochondrial gene were used to investigate genetic differentiation in B. terrestris, a bumble bee of interest for its high-value crop pollination. The analysis included eight populations from the European continent, five from Mediterranean islands (six subspecies altogether) and one from Tenerife (initially described as a colour form of B. terrestris but recently considered as a separate species, B. canariensis). Eight of the 10 microsatellite loci di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
275
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(308 citation statements)
references
References 48 publications
28
275
1
4
Order By: Relevance
“…However, the persistence of this effect into the second laboratory generation-as shown here-is more suggestive of a site-specific adaptation of the bees' gene expression patterns. This possible sign of local adaptation is especially noteworthy as the European B. terrestris population is panmictic [51,52]. The direction of the site effect differed among genes (electronic supplementary material, figure S3), whereas in the previous study [31], bees from Neunforn showed higher immune gene expression levels than bees from Aesch for all significantly differently expressed genes.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the persistence of this effect into the second laboratory generation-as shown here-is more suggestive of a site-specific adaptation of the bees' gene expression patterns. This possible sign of local adaptation is especially noteworthy as the European B. terrestris population is panmictic [51,52]. The direction of the site effect differed among genes (electronic supplementary material, figure S3), whereas in the previous study [31], bees from Neunforn showed higher immune gene expression levels than bees from Aesch for all significantly differently expressed genes.…”
Section: Discussionmentioning
confidence: 80%
“…We did not test the genetic diversity of our populations and any such differences may explain some of the differences we see between our two populations. However, given that all mainland European B. terrestris appear to be part of a single panmictic population [51,52], and the lack of any geographical barriers to gene flow between these populations, suggests that these two populations should not differ greatly in diversity.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the colony produces only half the normal quantity of workers from the start and thus will remain rather small in size, with low production of new queens. Second, as most bumble bee species are monandrous (even known polyandrous species mate with a frequency close to one; Estoup et al 1996;Payne et al 2003;Takahashi et al 2008) and diploid males produce diploid sperm, queens mating with diploid males produce 100 % of sterile triploid offspring leading to the inbred strain having much lower fitness than outbred colonies. In wild populations, this is known as the Bdiploid male extinction vortex^ (Zayed and Packer 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The large bumblebee Bombus terrestris is naturally distributed in Europe and adjacent territories, including England, most of Scotland, the north coast of Africa, southern Scandinavia, major Mediterranean islands, and some Atlantic islands (Madeira and the Canary Islands) (Estoup et al, 1996;Chittka et al, 2004;Velthuis and van Doorn, 2006). Since 1987, B. terrestris has been available commercially in portable boxes for crop pollination (Mitsuhata, 2000).…”
Section: Introductionmentioning
confidence: 99%